A structure-improved extended state observer based control with application to an omnidirectional mobile robot. (June 2020) - Ren, Chao; Ding, Yutong; Ma, Shugen
Abstract: This paper presents a structure-improved extended state observer (SESO) based trajectory tracking control scheme with application to an omnidirectional mobile robot. To alleviate the initial peaking phenomenon of the traditional extended state observer (TESO), a SESO with reduced order is proposed by improving the structure of TESO. Moreover, the designed SESO can achieve superior estimation performances. The total disturbances are estimated by SESO and then compensated in the controller. Then a phase-based nonlinear proportional–differential controller with time-varying gains is applied for high trajectory tracking performance. The stability of SESO and the closed-loop system are analyzed, respectively. Finally, the effectiveness of the proposed control scheme is validated through simulations in both frequency domain and time domain as well as experimental tests. Highlights: The proposed SESO can alleviate the initial peaking phenomenon. The estimation performances are improved by SESO. A tracking control scheme is proposed by combining a phase-based NPD and SESO. Bounded-input bounded-output stability is proved. Simulations and experimental results are presented.